Effectiveness of Cognitive Emotion Regulation on Emotional Intelligence in Students With Hearing Impairment - Mohammad Ashori; Azam Rashidi (Iranian Rehabilitation Journal, 2020)
Objectives: Cognitive emotion regulation plays an important role in the emotional intelligence of students with hearing impairment. The present study was conducted to determine the effect of cognitive emotion regulation on emotional intelligence in students with hearing impairment. Methods: The present study was a quasi-experimental research with pre-test-post-test and control group design. This sample consisted of 30 students with a hearing impairment aged 16-20 years from the deaf school of Mir in Isfahan City, Iran in the 2018-2019 academic year. They were selected by convenient sampling method. The subjects were randomly divided into the intervention and control groups, and each group consisted of 15 students. The intervention group received a cognitive emotion regulation program in 8 sessions (45 minutes per session), while the control group did not participate in this intervention and was kept in the waiting list. Data gathering tools were an emotional intelligence test, administered before and after the training sessions. The obtained data were analyzed using a multivariate analysis of covariance and analysis of covariance in SPSS. Results: The results indicated that cognitive emotion regulation had a positive and significant effect on emotional intelligence and its subscales of students with hearing impairment in the intervention group after the intervention (P<0.0001). Discussion: Cognitive emotion regulation improved the emotional intelligence of students with hearing impairment. This program facilitates the improvement of the emotional intelligence in these students. Thus, paying attention to the cognitive emotion regulation program is essential for students with hearing impairment.